4xy - 2y(x + 4) = 4xy - 2xy - 8y = 2xy - 8y = 2y(x - 4)
That depends on the plus or minus values of some of the terms in the expression that have not been given.
The answer to x2 - 2x - 4y2 - 4y =(x - 2y)(x - 2y - 2)
Collect like terms: 3x - x + 4x - 4y + 6y + 2 = 6x + 2y + 2
2xy - 4x plus 8y - 16 equals x plus 4 in parentheses multiplied by 2y minus 4 in parentheses. So, the factors are ( x + 4) and ( 2y - 4) .
-2y=x+8 is the answer
2y(x+2)=
Without an equality sign and not knowing the plus or minus values of 2y and 5 it can't be considered to be a straight line equation.
(2y - 5)(y - 2)
2+2y+x+xy=(x+2)(y+1)
Exactly (2y + 4) .
x=2y-1